O psicólogo nas políticas de proteção social: uma análise dos sentidos e da práxis - Botarelli, Adalberto (2008)
Analyzing the comeback of the debate on the role of the poor family in public policies, we can notice that the same is been required, again, to take over some cares of its members, due to the incapacity of the State in giving an answer to their needs. At the same time, it comes to evidence that the social problems linked with poor childhood and adolescence continue, increasing the amount of the citizens on a threatened situation for survival and denying a dignified life. - This evidence raises up the need to critically inquire on the role of this policies in the dialectic exclusion and inclusion that characterizes the social order in which it is included. This research aims to help with this analysis and its objective is to know the configuration of the sufferings and necessities of the families that run in an attendant program, it also tries to acknowledge in what amount the services delivered by the institutions are capable of potential emancipation of those attended, to overcome their suffering, or if the attendant program stands like a way of inclusion perverse and subtle . The theoretic-methodological referential of the socio-historic psychology was used to produce this research, outstanding the socio-historical conception of social order bound by the exclusion/inclusion dialectic and the categories of analyses of ethical-political sufferings and power of action, these categories show affectivity and necessity as ethical and political phenomena, overcoming the rupture between reason/emotion and individual/ society. In this way we analyze the relation between affectivity and ethical necessity looking forward on contributing with the debate on public policies of social inclusion nowadays adopted by guidelines and adjectives of public administration. The results of the research bring up the need to promote in the intervention programs directed to the family, changes in the conception of who is the subject of attendance. The analyses of the ethical-political suffering disclosed a human being affected by social determinations and with common needs, though lived in a particular way, a plural and collective human being with singular affective subtlenesses and not just homogeneous needs, so needing an attendance able to answer the singularities; listen to the clamor of suffering that can guide more embracing and articulated institutional actions with the other institutions as well as with the different programs of attendance, in order to fulfill public and private points of view , materialized in particular and collective needs. Finally, we conclude that it is up to develop theories and set forth interventions that favor the power of action, both in the intimate daily life dimension as well as public and politic. For that it is necessary to focus on affectivity, specially the emotions, because although being an intervention in the subjectivity area, it is about the fundamental locus of the policies of confrontation of social difference